A Clinical Conundrum in Anorexia Nervosa – Starvation Hepatitis vs Refeeding Hepatitis - Jwalamukhi Chidambaram Thirugnanam; Nikola Kern (BJPsych Open)
Aims: Anorexia nervosa (AN) is a severe eating disorder, with a lifetime prevalence estimated to be 0.3–0.9%. Transaminase elevations are common in patients during hospital admission, reaching a prevalence of 43%. Although usually caused by refeeding, prolonged starvation can also cause an exacerbation of liver enzyme levels. It is important to differentiate between the two, as the treatment plans are quite different. We herein present a report of a 34-year-old lady with anorexia nervosa, who presented with extreme worsening of liver functions due to starvation hepatitis, while on admission for refeeding and her gradual recovery.